A Marxist Approach to Communication Freedom - Slavko Splichal (tripleC: Communication, Capitalism & Critique)
This article is an abridged translation of the section “Produkcija in komuniciranje: nujnost in svoboda” (Production and communication: necessity and freedom) of Slavko Splichal’s book Množično komuniciranje med svobodo in odtujitvijo (Mass Communication between Freedom and Alienation, pp. 123-138), published in Slovene in 1981 after it was defended as a doctoral thesis in 1979. The article, which was among the earliest on its topic, starts with the discussion of Marx’s approach to the freedom of the press in his “Proceedings of the Sixth Rhine Province Assembly”, from the perspective of his later economic critique of capitalism, to show the inherent connection between human communication and work. This indissoluble connection is the starting point of the critique of “critical theories” aiming at “liberating” communication from work and production, exemplified by Habermas’s dualistic conception of work and communication. The concluding part discusses the relationship between communication freedom, rationality, and alienation, arguing that the freedom of communication cannot be founded on its independence from work (material production), but only on the emancipation or disalienation of human labour, and emphasising the danger that, if this does not happen, one-party socialist system with state and social ownership of the means of production and state-controlled economy will deteriorate into a multiparty capitalist system with private ownership and monopolistic economy. The article is followed by an afterword in which the author writes in a retrospect, after 40 years, about political and intellectual circumstances of the self-management socialism, which shaped the development of communication and media studies in “late socialism” – i.e. in the period preceding and heralding the collapse of socialism.